(2)-2(-6)=14

Simple and best practice solution for (2)-2(-6)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2)-2(-6)=14 equation:


Simplifying
(2) + -2(-6) = 14
2 + -2(-6) = 14

Multiply -2 * -6
2 + 12 = 14

Combine like terms: 2 + 12 = 14
14 = 14

Add '-14' to each side of the equation.
14 + -14 = 14 + -14

Combine like terms: 14 + -14 = 0
0 = 14 + -14

Combine like terms: 14 + -14 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7y-8+3y-1+y= | | 2514936.50+614593x=(3*648043)+648043x | | 2sinx+cosx=1 | | -13x+12=13x-13 | | 6(b-3)-3(2b-1)=2(b-9)-1 | | (X-9)(x+10)=90 | | -5x+12=-12x-12 | | (8*3.5)(.65B+.35A)=87.8 | | -5x+12=5x-5 | | (8*3.5)(.65A+.35B)=87.8 | | -5x+5=-5x+5 | | 4y-3=5+3y | | 3x(1.05)= | | 0.05n+0.1(63-n)=5.05 | | 4x/6=10/7 | | 36x^2-5=20 | | -17x=47x+120 | | F(x)=-2x^3+10x^3+48x | | 2+3+3*15= | | -5x=25x+80 | | 4x-5.58=-3.82 | | D+y=-9 | | (9b-13)(4b-9)=0 | | 3+4(x+y)=159 | | 7/3÷21/4 | | Y=-2(x-2)(x-5) | | 2=-3(2x+3)+7x | | F(x)=70x+40 | | 15x+10=10+10 | | 6+42=30 | | -6x+4y=-8 | | X=y(-2y+1)-5 |

Equations solver categories